BUKTI EMPIRIS TENTANG PENGARUH BUDGET RATCHETING TERHADAP HUBUNGAN ANTARA PENDAPATAN SENDIRI DAN BELANJA DAERAH PADA KABUPATEN/KOTA DI ACEH - Syukriy Abdullah; Afrah Junita (Modus, 2016)
This paper examines the effect of own revenues to expenditures and the effect ofbudget ratcheting as moderating variable in local government budgets. Using data from23 (twenty three) districts/cities in Aceh we find the own revenues have effect on localexpenditure and budget ratcheting may moderate the relationship between the ownrevenues and local expenditure.Keywords: Aceh agency problems, budgeting, budget ratcheting, city, fiscaldecentralization, local expenditure, local government, own revenue, regency.